Strategies to Increase Market Share for Histopathological Equipment Products (Brand Sakura): Case Study in a Sole Agent Company - Sukoco, Anton; Anshori, Yusak; Yudha, Ana Toni Roby Candra (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2020)
The purpose of this research is to evaluate marketing strategies that directly touch market leaders with to get marketing strategies to increase market share and become a market leader. This research uses qualitative and quantitative approaches. The analysis used was a descriptive analysis using the SWOT analysis instrument accompanied by IFAS and EFAS calculations. Data sources and types of research data consist of primary data and secondary data. Primary data were obtained from the results of focus group discussions, in-depth interviews, and questionnaires. Whereas secondary data was obtained from financial reports and relevant articles and literature. The results of the strategy enrichment using the SWOT analysis on the quantitative approach obtained that the company's position is in quadrant 3 namely WO quadrant with coordinates (-0.63; +1.47) so companies should implement a turnaround strategy, ie change their marketing strategy from direct hit to market leaders by improving after-sales service, improving the quality of their products, brand equity, support from top management and placing units in the Teaching Hospital. This research can provide practitioners with an overview in making strategic marketing decisions.